Standards-Based Teaching and Learning in a Catholic School: Benchmarking from the Standards of Quality in Basic Education - Marisa B. Petalla (Philippine Social Science Journal)
Amidst the crises faced by the Philippine educational system, several reform movements promote standards-based teaching and learning. This descriptive-comparative study determined if differences exist in the extent of implementation of standards-based teaching and learning in a senior high school program of a private university. The study utilized 46 teachers and a stratified random sample of 227 students who completed a modified research questionnaire. Mean, standard deviation, and one-way analysis of variance were employed in data analyses. The findings revealed excellent implementation as assessed by teachers and very good implementation as assessed by students. Further, significant differences were found in the extent of implementation when students were grouped according to strand, but no significant difference when teachers were grouped according to teaching experiences and educational qualifications. The findings of the study will be the basis for the formulation of the Content, Delivery, and Assessment (CDA) Plan.